Analisis Kebutuhan Pengembangan Media Pembelajaran Alat Peraga Berbahan Daur Ulang dan Digital untuk IPAS Kelas IV - Anggraini, Lussy (Jurnal Didaktika Pendidikan Dasar, 2025)
Learning media play an essential role in the teaching and learning process in the classroom. Without appropriate learning media, classroom learning can feel dull and monotonous, especially for children with a cognitive learning style. Students may find it challenging to grasp the information provided by the teacher. This study aims to identify the needs of teachers and students in the fourth grade at SD Negeri Sawit related to the subject of IPAS (Natural and Social Sciences) with the topic of Indonesia’s landforms. The researcher used the ASSURE model (analyze learners, state objectives, select media, materials, and methods, utilize media, materials, and methods, require learner participation, evaluate and revise). This study did not fully implement the ASSURE model and stopped at the third stage, which is Utilize media, materials, and methods. The results showed that teachers and students have not yet integrated concrete learning media, especially in the topic of Indonesia’s landforms. It can be concluded that learning requires media that are inexpensive and easily accessible. Processing used goods into learning media can be an option to create learning media that is simple, affordable, environmentally friendly, and inclusive, adjusted to the conditions of the targeted classroom.